Islam Karimov as a daring initiator and confident catalyst of conducive alterations in Uzbekistan - Mirsalikhova Robiya Timurovna (Zien Journals, 2024)
It is universally acknowledged that not all prominent people are associated with the words, audacious, accountable, unbiased, impartial, and admirable. World history presents such a chance to many, but not everyone realizes it fully. Only ingenious, extraordinary and charismatic personalities who produce an epochal sensation on the course of events throughout the world occupy their exclusive place in the history of mankind. Islam Karimov is undoubtedly refers to this sort of people. Given article is dedicated to profoundly discuss and examine the contributions made by Islam Karimov to the progress of Uzbekistan in diverse spheres of life.
Keywords: economics; independency; reforms and regulations; social constructions